Managerial Ability as a Mechanism for Creating Firm Value through Risk Management - Richard Wiratama; Suwandi NG (The Indonesian Journal of Accounting Research, 2021)
This study investigates the role of managerial ability on the creation of firm value which is tested directly and indirectly through risk management. This research model was built based on resource-based view theory dan stakeholder theory. The population in this study was all companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sample used in this study was 183 non-financial companies, which was selected by the purposive sampling method. This study uses documentary data, i.e., the annual report and financial statements. Path analysis was used to analyze the data, and the mediation hypothesis was analyzed using the Sobel mediation test. The results of this study indicate that 1). The managerial ability has a positive and significant impact on risk management; 2). The managerial ability has a positive and significant impact on firm value; and 3). The implementation of risk management can fully mediate the impact of managerial ability on firm value. The implications of this study are expected to provide theoretical implications for the development of science in the field of accounting and management regarding the factors that affect firm value. Implications practice of this research is as learning for companies and investors to consider the importance of risk management through managerial ability as a mechanism to create firm value.